2020
DOI: 10.32615/ps.2019.132
|View full text |Cite
|
Sign up to set email alerts
|

Special issue in honour of Prof. Reto J. Strasser - Structural and functional response of photosynthetic apparatus of radish plants to iron deficiency

Abstract: In this work, we tried to identify some specific chlorophyll a fluorescence (ChlF) parameters, that could enable detection of iron deficiency (Fedef) in radish plants (Raphanus sativus L.), before any visual symptoms appear. Changes in ChlF kinetics, JIP-test parameters, and chlorophyll content revealed that iron deficiency negatively affected PSII activity mainly via disruption of light absorption in light-harvesting complexes and by decreasing the activity of the primary quinone acceptor of PSII (Q A). Iron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…Several earlier studies demonstrated the suboptimal development of the photosynthetic apparatus under nutrient shortage and the resulting reductions of PSII photochemistry [35][36][37]. Recently, Samborska-Skutnik et al [38] demonstrated that Fe deficiency negatively impacted PSII functioning by disrupting light absorption, as well as decreasing the activity of Q A , which is the primary quinone acceptor. In the control plants of the present work, the conservation of energy absorbed by the antenna of PSII, as indicated by the PI abs index, as well as the total photosynthetic efficiency (PI total index), were significantly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Several earlier studies demonstrated the suboptimal development of the photosynthetic apparatus under nutrient shortage and the resulting reductions of PSII photochemistry [35][36][37]. Recently, Samborska-Skutnik et al [38] demonstrated that Fe deficiency negatively impacted PSII functioning by disrupting light absorption, as well as decreasing the activity of Q A , which is the primary quinone acceptor. In the control plants of the present work, the conservation of energy absorbed by the antenna of PSII, as indicated by the PI abs index, as well as the total photosynthetic efficiency (PI total index), were significantly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…The maximum quantum yield (F v /F m ) is an essential indicator of algal cell health status. Changes in F v /F m have been observed when algae are exposed to endogenous or exogenous stressors, such as light [52,70,71], temperature [71], salinity [72], iron and algistat addition [73][74][75][76]. A significant decline in F v /F m of C. marina and C. ovata was shown in the present study under high light (Figure 3), in the dark (Figure 7), under iron depleted conditions (Figure 9) and the presence of PSII inhibitors (Figure 11), suggesting inactivation of PSII reaction center (RC) complexes and disruption of the electron transport chain [77,78].…”
Section: Toxinological Mechanism Of Hemolytic Activitymentioning
confidence: 99%
“…Chlorophyll a fluorescence measurements are used to monitor the physiological condition under environmental stresses of all photosynthetic organisms (Živčak et al, 2014;Goltsev et al, 2016;Kalaji et al, 2016;Kalaji et al, 2018b;Samborska et al, 2018;Samborska et al, 2019;Loudari et al, 2020;Samborska-Skutnik et al, 2020;Vukelić et al, 2021). There are many examples of successful application of ChlF for studying the reaction of photosynthetic apparatus to high and low temperature (Alam, Nair and Jacob, 2005;Oukarroum, Goltsev and Strasser, 2013;Kalaji et al, 2018a), drought (Goltsev et al, 2012;Dąbrowski et al, 2019), salinity (Kan et al, 2017), heavy metals (Azevedo, Glória Pinto and Santos, 2005;Bayçu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%